Application Of Composite Materials and Metal Powders in the Technology of Restoration of Worn Parts - Ikromov Nurullo Avazbekovich (Zien Journals, 2022)
We can now say with confidence that we have begun to move from the “iron” age to the age of composite materials.
Keywords: metallokeramik; keramiklar; metall-polimer